2021
DOI: 10.1101/2021.03.25.436883
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural circuitry for maternal oxytocin release induced by infant cries

Abstract: SummaryOxytocin is a neuropeptide important for maternal physiology and childcare, including parturition and milk ejection during nursing. Suckling triggers oxytocin release, but other sensory cues- specifically infant cries- can elevate oxytocin levels in new human mothers, indicating that cries can activate hypothalamic oxytocin neurons. Here we describe a neural circuit routing auditory information about infant vocalizations to the oxytocin system of the mouse brain. We performed in vivo electrophysiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 151 publications
(340 reference statements)
1
25
0
Order By: Relevance
“…While in both rodent species primary sensory cortices do not project to OT neurons, secondary sensory areas, such as the posterior and auditory thalamic nuclei do (Dobolyi et al, 2018 ; Valtcheva et al, 2021 ). This suggests that sensory information in rodents is conveyed to the OT system via secondary pathways, which could explain the activation of OT neurons by diverse sensory channels involved in social communication such as tactile (Tang et al, 2020 ) and auditory stimuli (Valtcheva et al, 2021 ), fear (Hasan et al, 2019 ), pain (Eliava et al, 2016 ), and reproductive and parental behaviors (Scott et al, 2015 ). However, we still do not know whether OT neurons and/or their subpopulations can be categorized based on their specific inputs (as well as outputs; Hasan et al, 2019 ).…”
Section: Do Ot Neurons Receive Feedback Projections From Their Targets?mentioning
confidence: 99%
“…While in both rodent species primary sensory cortices do not project to OT neurons, secondary sensory areas, such as the posterior and auditory thalamic nuclei do (Dobolyi et al, 2018 ; Valtcheva et al, 2021 ). This suggests that sensory information in rodents is conveyed to the OT system via secondary pathways, which could explain the activation of OT neurons by diverse sensory channels involved in social communication such as tactile (Tang et al, 2020 ) and auditory stimuli (Valtcheva et al, 2021 ), fear (Hasan et al, 2019 ), pain (Eliava et al, 2016 ), and reproductive and parental behaviors (Scott et al, 2015 ). However, we still do not know whether OT neurons and/or their subpopulations can be categorized based on their specific inputs (as well as outputs; Hasan et al, 2019 ).…”
Section: Do Ot Neurons Receive Feedback Projections From Their Targets?mentioning
confidence: 99%
“…16 OXT action results in modulation of neuronal activity in brain areas regulating social behaviors 17 to increase the salience and reinforcing value of social stimuli. 18,19 Furthermore, OXT neurons are activated in response to social stimuli including social touch, 20 infant cries, 21 and mating. As a relationship develops, these events offer an opportunity for the OXT system to modulate the expression of the social bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Social behavior in mammals is quite distinct from fish, so that a direct comparison between previous results and ours is hard to draw. Previous studies have convincingly shown that Pth2 contributes to maternal behavior (Cservenák et al, 2010(Cservenák et al, , 2013Gellén et al, 2017;Dobolyi, Cservenák and Young, 2018) and the posterior intralaminar thalamus, where one of the thalamic Pth2+ populations is found in mammals, integrates social cues, eventually activating oxytocinergic neurons (Cservenák et al, 2017;Dobolyi, Cservenák and Young, 2018;Valtcheva et al, 2021).…”
Section: Discussionmentioning
confidence: 98%